Transaksi Dropshipper Melalui E-Commerce: Studi Takhrij dan Syarah Hadis - Kamilah, Nabila Fairuz Putri (Jurnal Riset Agama, 2021)
This study aims to analyze the hadith about dropshipper transactions through e-commerce. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods with contemporary analysis. The results of this study found that the quality status of this dropshipper transaction was considered authentic based on the takhrij hadith. Syarah hadith shows that dropshipper transactions if a salam contract is used, then the transaction is valid and may be carried out with an agreement that has been made with the supplier. However, if the seller does not mention himself as a dropshipper then it is prohibited, because there is no agreement and there is an element of fraud (gharrar). This study concludes that the hadith about dropshipper transactions through e-commerce is acceptable (maqbul) so that it can be used as evidence for Islamic practice. This study recommends that a review be carried out through the approach of hadith science and economics related to dropshipper transactions in terms of processes and objects if you want to transact as a dropshipper with sharia provisions.